Chameleon cosmology: the nonminimal coupling function from the observational data - Bakirova, E.M.; Folomeev, V.N. (Recent Contributions to Physics, 2015)
Using the cosmological and astronomical observational data, the general expression for the nonminimal coupling function  between a scalar field and matter (ordinary and/or dark) is obtained within the framework of chameleon cosmology. The scalar field is assumed to be homogeneously and isotopically distributed over spacetime. The effective mass of the scalar field is taken to be small on cosmological scales, but it increases in the dense environment (on Earth). This allows the laboratory tests and experiments in the solar system to be satisfied. The expansion rate of the present Universe is approximated by the Hubble parameter, which is chosen here using the model “cosmological -term plus cold dark matter”. In the case of massless scalar field, for such an ansatz the analytical expression for  valid for the present Universe is found.
Keywords: chameleon cosmology; scalar field